Corrosion Behavior in External Surface of API 5L X52 Underground Pipelines in Buzurgan Region/ Missan province - Alsultani, Kadhim F.; Mutasher, Zahraa Qasim (Journal of Petroleum Research and Studies, 2021)
External corrosion of underground pipeline is one of the most common damage mechanisms associated with the soil environment particularly in ageing pipelines. This study investigates the external corrosion phenomenon for exporting crude oil pipeline (28’’) in Buzurgan region / Missan province. Corrosion rate was measured by using weight loss method, and Tafel extrapolation. Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were also used in this work. During the field survey, soil sample was taken from Buzurgan region (collected as close as possible to buried pipes at 1.2 m) for tests were carried out for soil that included: pH, moisture content, resistivity and chemical composition (XRF, XRD, and soluble salts). It was found that the environment of the areahas a low soil resistivity value (870) ohm.cm. On other hand, the samples that were immersed in Buzurgan soil showed the that highest damage was by pitting corrosion due to the high soluble salts content particularly chlorides (7388 )ppm and sulfates (2570) ppm.